Synchronisation of breeding in populations of the brown mussel Perna perna on the South Coast of South Africa - Ndzipa, Victoria (Rhodes University, Faculty of Science, Department of Zoology and Entomology)
The general biology and seasonality of breeding of intertidal populations of the brown mussel Perna perna in South Africa are reasonably well known, but we have little information on variability either within or among populations. Synchronous spawning offers adaptive advantages to externally breeding animals. Firstly, it enhances fertilization rates and therefore the species' reproductive fitness. Secondly, spawning can also be timed to coincide with environmental conditions conducive to larval settlement and development. In addition, synchronisation of spawning will influence the synchrony of settlement. Synchronisation of larval settlement, in turn, has implications for popUlation biology, as highly pulsed settlement is likely to lead to density-dependant mortality of recruits and uncoupling of adult/recruit densities, while poorly synchronised settlement will not. Generally, sea temperature and food availability are considered the key factors underlying the initiation and the duration of the breeding cycle of mussels. However, there are proximate local cues that trigger the proliferation, maturation and release of gametes. In this study, the hypothesis tested is that factors that control food availability affect gonad development and so influence synchrony among populations. Much of the published work on spawning is based on observations of the presence of larvae in the plankton, or on settlement. A more reliable method correlates the sequence of gonad development throughout the year with changes in length-weight relationships, using histology. This study is also designed to investigate temporal differences in the timing of the breeding cycle between sheltered and exposed sites along the south coast of South Africa by histological analysis of the reproductive tissue (the gonad) and by dry weight/shell length regreSSIOns. To do this, these two techniques were applied to six mussel populations at three III ocalities that were separated on scales of about 10-20km. Within each locality, two study sites were .dentified. One was exposed to strong wave action and one was sheltered. A few hundred meters ;eparated these sites. The first technique used length-weight regressions as an indication of mussel ~ondition. Abrupt decreases in the dry body weight of a hypothetical standard animal were taken to indicate periods of spawning. Regressions were assessed for samples of 40 mussels taken from each site at intervals of 4 weeks over 13 months. The results were analysed using a 3-way ANCOV A, with dry weight as the dependent variable, shell length as a covariate, and site, exposure and month, as independent variables. The second approach used the more reliable and detailed method of assessing the annual reproductive cycle using histological sections of the gonad. Histological sections of gonads from thirty female mussels, sampled monthly from each site, were examined in the laboratory. Each gonad was categorized into one of six arbitrary developmental stages based on ovary morphology. Synchrony in spawning was examined by comparison of gonad developmental stages of individuals within and among populations. The data were analysed by 3-way nested ANOV A with mean gonad index for each population as the dependent variable, month as an independent variable and exposure nested in site. The results obtained from both techniques showed strong synchronisation among different popUlations, regardless of the scales at which they were separated. The data also indicated good synchrony within populations and, again among populations, regardless of the degree of exposure. The results also indicated that the gonad condition varied significantly at each site, exposure level and month. However, there were significant interactions among these three factors. This means that on a broader seasonal scale the six mussel populations were reasonably synchronised, but on finer monthly scales, there were temporal differences in duration of gametogenic events. The implication is that ovary development is cued by environmental factor(s) that operate on scales of at least 7-20 km rather than more localised events that may affect food availablity either through aggregation of food (local hydrography at different localities) or food delivery to the shore (degree of wave action at different sites.),KMBT_363,Adobe Acrobat 9.54 Paper Capture Plug-in
Keywords: Mussels -- South Africa; Perna -- South Africa; Perna -- Breeding